Intelligent work adjustment approaches of new academics - Abdul Wahat, Nor Wahiza; Nasir, Rohany; Omar, Fatimah (Eurojournals, 2009)
Malaysian public universities have been entrusted with the responsibilities to generate first class human capital, promote the banner of lifelong learning and create new knowledge as well as innovations. This has made the learning of academia ropes even tougher for new academics. Intelligent work adjustment approaches and strategies are very much needed to set the right career bearings and job satisfaction during their early years of service. A qualitative research has been conducted to examine the work adjustment approaches and strategies adopted by new academics in three public universities. Results from in-depth interviews on twenty three new academics showed that intelligent career navigation, which involves three ways of knowing (‘why we work’, ‘how we work’ and ‘with whom we work’) play very essential role to ensure smooth, successful work adjustment of new academics. Needs-supplies fit perception, combination of active and reactive work adjustment style and the personality of ‘extraversion’ have emerged as the three important sub-themes within the major theme of intelligent career navigation.